Celtic pilgrimage, past and present: from historical geography to contemporary embodied practices. (17th February 2016) - Maddrell, Avril; Scriven, Richard
Abstract : Perigrinatio, the Latin term for pilgrimage was at the heart of the medieval Celtic church, but was this was understood and practised not only as a journey to a shrine, but more broadly as a spiritual journey, which could lead to an isolated hermitage or peripatetic evangelistic mission. In this paper, we outline the beliefs and practices of the broad assemblage known as the Celtic church, particularly the interleaving of pilgrimage, asceticism and landscape poetics, and how these have informed continued and renewed pilgrimage practices to sites of the early Celtic church by particular denominations, ecumenical groups and those interested in broader spiritualities. These sacred mobilities are explored through vignettes of embodied-emotional-spiritual practices situated in the landscapes and faith communities of Lough Derg, Ireland and the Isle of Man. They share geographical marginality, a focus on multiple Celtic saints and an enduring belief in the immanence of God, expressed through embodied spiritual practice in the landscape. However, they differ widely in matters of institutionalised structure, regulation, discursive scripting and gendered hierarchy, reflecting situated and denominational preferences for the ascetic and aesthetic spiritual legacies of the medieval Celtic church.